ON THE OCCURRENCE OF ANCHOVIELLA BAGANENSIS (HARDENBERG) AND A. BATAVIENSIS (HARBENBERG) ALONG THE SOUTH-EAST AND SOUTH-WEST COASTS OF INDIA - George, K C (Indian Journal of Fisheries, 2016)
Three Species of white-baits (Genus: Anchoviella) were described by Day(1878-89) from Indian waters under the generic name Engraulis Cuvier,1817; viz., E. commersonianus (Lacepede, 1803), E. indicus (van Hasselt, 1823),and E. tri (Bleeker, 1852). Weber and de Beaufort (1913) recognised fivespecies from the Indo-Australian archipelago, but used the generic nameStolephorus Lacepede, 1803. Important contributions to the knowledgeof the systematics of these fishes have been made by Hardenberg (1933 and1934) and by Fowler (1941). It was Fowler (1911) who emended StolephorusLacepede (strictly belonging to subfamily Dussumieriini, Clupeidas) andcreated the new genus Anchoviella (Engraulidae) with Engraulis perfasciatusPoey, orthotypic as the genotype.